2008
DOI: 10.1128/iai.00192-08
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm-Induced Persistent Changes to the Immunological Environment of the Lung

Abstract: A number of important helminth parasites of humans have incorporated short-term residence in the lungs as an obligate phase of their life cycles. The significance of this transient pulmonary exposure to the infection and immunity is not clear. Employing a rodent model of infection with hookworm (Nippostrongylus brasiliensis), we characterized the long-term changes in the immunological status of the lungs induced by parasite infection. At 36 days after infection, alterations included a sustained increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 69 publications
2
66
0
Order By: Relevance
“…On the other hand, it is also possible that the active concentrations of both RELM proteins may be different, which could impact the biological significance of the different concentrations of these proteins in different tissues. Even though N. brasiliensis is expelled between day 9 and day 12 postinfection in WT mice, previous studies have shown long-lasting inflammatory changes in infected tissue even following worm clearance (21)(22)(23). At day 30 postinfection, we observed increased RELM␣ levels in serum and all infected tissues, while the RELM␤ level was significantly increased in serum, suggesting that N. brasiliensis infection induces persistent changes in RELM␣ and RELM␤ expression levels that may be functionally significant.…”
Section: Kinetics Of Relm␣ and Relm␤ Expression Following N Brasiliementioning
confidence: 41%
“…On the other hand, it is also possible that the active concentrations of both RELM proteins may be different, which could impact the biological significance of the different concentrations of these proteins in different tissues. Even though N. brasiliensis is expelled between day 9 and day 12 postinfection in WT mice, previous studies have shown long-lasting inflammatory changes in infected tissue even following worm clearance (21)(22)(23). At day 30 postinfection, we observed increased RELM␣ levels in serum and all infected tissues, while the RELM␤ level was significantly increased in serum, suggesting that N. brasiliensis infection induces persistent changes in RELM␣ and RELM␤ expression levels that may be functionally significant.…”
Section: Kinetics Of Relm␣ and Relm␤ Expression Following N Brasiliementioning
confidence: 41%
“…Infection with Nb results in a number of immediate and longterm changes to the immunological status of the lungs, including quantitative and phenotypic changes in the macrophage population [10,13,17,42]. In the current study, we describe two distinct morphological forms that develop within the lung macrophage population after a hookworm infection-a vacuolated, foamy phenotype that was supplanted within a few days PI by a persistent population of enlarged macrophages that contained dense granules in the cytoplasm (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…It is not clear if the origin of these cells is connected. Although it is possible that foamy macrophages transform into the cells with the granular morphology, it is equally likely that these distinct cell types represent at least two different populations whose phenotypes are influenced by the dynamics of the cellular and cytokine changes that persist in the PI lung environment [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important associated feature of Nb infection is the significant damage to the epithelium and vasculature of the lung resulting from worm penetration and subsequent migration through the parenchyma into the airways 2,9 . In a primary infection, the host immune response to these events appears too slow to affect worm survival or fecundity.…”
mentioning
confidence: 99%